Longitudinal assessment of oral intake adequacy and nutrition-impacted symptoms in patients undergoing allogeneic hematopoietic stem cell transplantation - Qin, Liyuan; Li, Rui; Wu, Jiaqi; He, Yang (Frontiers in Nutrition, 2025)
AimsThis study aims to longitudinally assess the adequacy of oral intake and burden of nutrition-impacted symptoms (NIS) and identify modifiable factors associated with oral intake adequacy in allogeneic hematopoietic stem cell transplantation patients.MethodsA single-center prospective study enrolled allogeneic hematopoietic stem cell transplantation patients from May 19, 2022 to February 8, 2023. We evaluate the adequacy of oral intake and nutrition-impacted symptoms in the peritransplantation period. Generalized estimating equations were adopted to evaluate associated factors of the adequacy of oral energy and protein intake.ResultsA total of 63 allogeneic hematopoietic stem cell transplantation patients were enrolled in the study, with 439 records. The adequacy of oral energy/protein intake showed a trend of decreasing first and then increasing, and 57.1–95.2% of the patients suffered from at least one nutritionally impacted symptom in the peritransplantation period. Generalized estimating equations indicated that the presence of nutrition impacted symptoms was a risk factor significantly associated with the adequacy of oral energy intake <50%, while the use of oral nutrition supplements was a protective factor. There were similar associations between the adequacy of oral protein intake <50% and the above two factors.ConclusionInsufficient oral energy and protein intake and the burden of nutrition impacted symptoms in peritransplantation patients are common, and further attention and intervention on these issues are needed. Oral nutrition supplements are a potential approach to increase oral intake and nutritional status in allogeneic hematopoietic stem cell transplantation patients.